The Effect of Otaria Exercise for Perineal Wounds in Postpartum Women in the Karang Intan 2 Health Center Banjar South Kalimantan - Kirana, Rita; Tut Barkinah; Januarsih; Agus Rachmadi; Suhrawardi; Isrowiyatun Daiyah (MultiTech Publisher, 2024)
One of the causes of maternal mortality is infection during the puerperium at 11%. Infections during the puerperium can come from birth canal openings which are a good medium for germs to develop. This researh used a Quasi-experiment approach. Respondents were divided into 2 groups, control group who did not perform Otaria exercises and treatment group who performed Otaria exercises. The p value <0.05, meaning that there is an effect of Otaria exercises on Perineal Wound Healing in postpartum women in the Karang Intan 2 Health Center area. Otaria exercises can improve blood circulation to the perineum, the state of clean oxygen-rich blood is expected to help in the healing process of perineal suture wounds.